Identifying the Level of Effective Leadership Practices : An Analytical Research in "The Office of Iraqi Interior Ministry " - A. tamemi , Haidar; Jassim Mohammed, Nisreen (Journal of Economics and Administrative Sciences, 2023)
The current research aims to identify the level of effective leadership practices dimensions (clear vision and specific goals, good planning and effective influence, and monitoring well as evaluation) among the senior leaders in the Office of the Iraqi Interior Ministry., The researchers adopted the descriptive analytical approach to collect data through the questionnaire as a main tool, developed by relying on international standards after making adjustments to its items consisting of (25) items that included the research variable, the questionnaire was distributed to all the research community (comprehensive inventory) by 120 forms from employees working at the level of (ahead of the directorate, and ahead of department), to recover 105 forms, but the good forms for the final analysis were 102 forms, form, using statistical programs (SPSS V.28 (, including (mathematical averages, standard deviation, difference factories, and relative importance, and the research reached the most prominent result represented by the existence of this leadership practices with the senior leadership of the Office of the Iraqi Interior Ministry. Paper type: Research paper